Perempuan Pebisnis Startup di Indonesia dalam Perspektif Cybertopia - Ayu, Rizka Kurnia (Jurnal Studi Komunikasi, 2017)
Â This research aim to show the internet from cyberthopia perspective to discribe that the dogma in the society such as technologi as man extenions, It is not entirely true. To support this research,Â  ten indonesian statrtup women, with income hundreds of millions per month, were chosen as the main object in this research. Furthermore, the results of this study show that the Internet has blurred the gender boundary between femininity and masculinity. The statement of the existence of a man is no longer fully valid with the great success that has been achieved by these ten business startup women as economic agents of the family without releasing identity as a female figure.Â